Analisa Penggunaan Superconducting Fault Current Limiter (SFCL) Untuk Melindungi Peralatan di PT Pindo Deli - Yohanes Sabriant Widyo Utomo; Margo Pujiantara, Arif Musthofa (Jurnal Teknik ITS, 2015)
Increas demand load and power capacity requirement at PT Pindo Deli then the short circuit current that occur will be greater. this can cause damage to electrical equipment located around the point of interrupting and resulting failure of the electrical system in power distribution. from the analysis of the three phase short circuit current 1/2 cycle seen that the bus 1 exceeds the peak breacing  asimetry equipment.  Where breacing peak bus asymetri 1 was 43.88 kA. While the peak of 3-phase  short circuit on the bus 1 is 47.98 kA.  To protect the equipment and the entire electrical system in PT Pindo Deli would require  the use of Superconducting Fault Current Limiter (SFCL) that will be placed on buses that  exceed or approach the critical point. There are two kinds of Superconducting Fault Current Limiter that type of resistive and saturated iron core. In this final project SFCL used  is a hybrid resistive Superconducting Fault Current Limiting. By using a hybrid resistive  SFCL then flow disturbance will quickly be reduced by utilizing the reactance of Current  Limiting Reactor (CLR) that is connected parallel with superonductor So as to secure all the equipment and electrical systems of a total blackout. After determination of Superconducting Fault Current Limiter setting the overcurrent relay coordination to determine whether existing coordination setting in accordance with the conditions there.  The coordination displayed using the curve Current Time Curve (TCC).